A Retrospective Comparison of Antibiotic Regimens for Preterm Premature Rupture of Membranes - Pierson, Rebecca C. (2014)
OBJECTIVE: To evaluate whether the use of ampicillin and azithromycin leads to a similar latency period in preterm, premature rupture of membranes (PROM) as ampicillin and erythromycin, and whether the substitution of azithromycin for erythromycin effects rates of other outcomes. METHODS: We performed a retrospective cohort study of women with preterm PROM between 24 and 34 completed weeks and compared two groups: those who received ampicillin and erythromycin to those who received ampicillin and azithromycin. Primary outcome was length of latency (defined as time from first antibiotic dose to delivery) and secondary outcomes were rates of chorioamnionitis, cesarean delivery, APGAR scores, birth weight, neonatal death, neonatal sepsis, and neonatal respiratory distress syndrome. RESULTS: Of 168 women who met inclusion criteria, 75 received ampicillin and erythromycin and 93 received ampicillin and azithromycin. There was no difference in latency between groups: 9.6 ± 13.2 days (erythromycin) versus 9.4 ± 10.0 (azithromycin) days (p=0.40). Secondary outcomes did not differ between groups. We had 80% power to detect a difference of 5 days. CONCLUSIONS: Among women with preterm PROM between 24 and 34 completed weeks, substitution of azithromycin for erythromycin in the recommended antibiotic regimen did not impact latency or any other measured maternal or fetal outcomes.